Riqueza e abundância de formigas (Hymenoptera: Formicidae) em diferentes classes de solo em uma área de savana próxima de Boa Vista-RR - Cidade, Márcia Patrícia Nascimento (2011)
Savanna (Lavrado) of Roraima occupy 17% of its territory. These areas have a mosaic of vegetation and pedological diversity due to factors of soil formation. The ants are present in virtually all terrestrial environments, and playing numerous roles in the ecosystem. The objective of this research was to evaluate the relationships between the physical and chemical characteristics of soil with ant assemblages in a savanna area near Boa Vista, Roraima (Campus Cauamé/UFRR). The study was conducted in 12 permanent plots of the Biodiversity Research Program (PPBio). We used two techniques (baits and pitfalls), and 10 sub-samples from each plot, 25 m apart from each other, a total of 120 sub-samples using the method of collection. The pitfalls remained in operation for 48 hours and the baits were exposed for 40 minutes. The material was collected and taken to the laboratory for identification. The chemical and physical soils were obtained from the metadata available from the PPBio. Additionally we collected moisture content and resistance to penetration (RP). Data from the soil classes were obtained from detailed studies of Cauamé campus. Ant assemblages were sorted based on the presence / absence of individuals using non-metric multidimensional scaling (NMDS). To check the influence of environmental variables on the distribution of ants, we performed a Multivariate Analysis of Variance (MANOVA). The similarity between the techniques was analyzed with the Mantel test. In the study area were identified five classes of soil, and these were collected 8,936 ants distributed in 7 subfamilies, 22 genera and 49 species which are 39 morphotypes. The species Kalathomyrmex emery was first recorded for the state of Roraima. The most abundant genera were found in the bait Crematogaster (46.3%) and Camponotus (25.5%). The similarity between the techniques and bait pitfall was low (35%), but the pitfall was 92% similar the two techniques together. Among the environmental variables tested, we found that there was no significant difference in the classes of soil, moisture and pH with the distribution of ants, and the clay was the only variable that influenced the distribution of ants. The pitfalls may be the only method of collecting ants in savanna areas. The highest species richness of ants was found in the Yellow Latosol. And the soil with less wealth was the Gleysol, however, was the soil with the highest number of exclusive species.